2019
DOI: 10.14744/anatoljcardiol.2019.45845
|View full text |Cite
|
Sign up to set email alerts
|

Normal echocardiographic measurements in Turkish population: The Healthy Heart ECHO-TR Trial

Abstract: Objective: Normal reference values for the cardiac chambers are widely based on cohorts from European or American populations. In this study, we aimed to obtain normal echocardiographic measurements of healthy Turkish volunteers to reveal the age, gender, and geographical region dependent differences between Turkish populations and other populations. Methods: Among 31 collaborating institutions from all regions of Turkey, 1154 healthy volunteers were enrolled in this study. Predefined protocols were used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…In conclusion, the current data obtained from healthy Turkish volunteers are comparable with most previous studies in this era (2,3,5,6,10,11,13,18). E and A waves of mitral annulus and also E/A ratios were greater compared to European registries, but these differences were not statisitically significant.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, the current data obtained from healthy Turkish volunteers are comparable with most previous studies in this era (2,3,5,6,10,11,13,18). E and A waves of mitral annulus and also E/A ratios were greater compared to European registries, but these differences were not statisitically significant.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, the current data obtained from healthy Turkish volunteers are comparable with most previous studies in this era 2,3,5,6,10,11,13,18 . E and A waves of mitral annulus and also E / A ratios were greater compared to European registries, but these differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, we, for the first time in Turkey, have reported two‐dimensional echocardiographic normal reference ranges for cardiac chamber quantification in a large cohort of Turkish individuals 5 . Besides the chamber sizes, essential data regarding the relationship between these measurements and age, gender, body surface area and geographical region‐dependent differences have been provided.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the Japanese Normal Values for Echocardiographic Measurements Project (JAMP) study examined 700 healthy Japanese subjects and found that LV dimensions were larger for males than for females, but also showed that values for males were smaller when indexed to BSA, and that 2D LV volume for males was larger than for females even when the values were indexed to BSA [8]. Most of the subsequent national or regional studies on normal reference values for LV size showed results consistent with those of the JAMP study [9][10][11][12][13][14][15][16], while some showed only minor differences [17]. As for the relationship between LV size and age, 2D LV volume generally decreased with age for both genders [8,11,16,[18][19][20], which has been confirmed in a meta-analysis based [21].…”
Section: Sizementioning
confidence: 66%
“…LaBounty et al, on the other hand, reported that LV dimensions for Asians and Hispanics were larger than those for Whites [22]. Some other studies suggest that slight differences exist in normal values for LV size even within a single race or country, so that place of residence may also play a role [17,23]. Recently, the WASE Normal Values study used a uniformed measurement protocol to examine in two core laboratories data for over 2000 normal subjects enrolled worldwide, and found only minor differences for LV size among races and countries, although the normal reference values recommended in the current guidelines need to be adjusted [15].…”
Section: Sizementioning
confidence: 99%